2012
DOI: 10.1111/j.1440-1819.2012.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Urine catecholamine levels are not influenced by electroconvulsive therapy in depression or schizophrenia over the long term

Abstract: Aim: Change in catecholamine seems to be associated with not only effects of electroconvulsive therapy (ECT), but also adverse events associated with ECT. Our aim in this study was to investigate whether or not ECT influences the concentration of catecholamine over the long term. Patients with a major depressive episode or schizophrenia, diagnosed according to DSM-IV criteria, who were newly admitted to Juntendo University Hospital to receive ECT, were recruited.Methods: Urine was collected during the 24 h bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…However, the results of Saijo et al 16 showed that no significant differences were observed in 5-HT 1A receptor binding before and after ECT, a result that challenges the hypothesis that ECT may enhance the transmission of serotonin. A biochemical study conducted by Ito et al 48 , which showed no significant differences in dopamine levels 1 week after a course of ECT, also supports this view. 46 This result also suggests that ECT may not act by enhancing dopamine neurotransmission, as antidepressant drugs are thought to do.…”
Section: Ect and Neurotransmittersmentioning
confidence: 72%
“…However, the results of Saijo et al 16 showed that no significant differences were observed in 5-HT 1A receptor binding before and after ECT, a result that challenges the hypothesis that ECT may enhance the transmission of serotonin. A biochemical study conducted by Ito et al 48 , which showed no significant differences in dopamine levels 1 week after a course of ECT, also supports this view. 46 This result also suggests that ECT may not act by enhancing dopamine neurotransmission, as antidepressant drugs are thought to do.…”
Section: Ect and Neurotransmittersmentioning
confidence: 72%
“…Different neural networks may be activated depending on the seizure propagation. 42 Today, there are no studies available to examine the effects of MST on catecholamines. Compared with ECT, MST is believed to only stimulate focal superficial cerebral cortex, 37 and it may induce a generalized seizure through anatomical links and functional connections, which is less likely to affect locus coeruleus in the deep brain area.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ECT may cause a short-term rise in catecholamine and which diminishes over 24 hours. Different neural networks may be activated depending on the seizure propagation 42 . Today, there are no studies available to examine the effects of MST on catecholamines.…”
Section: Discussionmentioning
confidence: 99%
“…Ein direkter Einfluss der EKT über eine vermehrte Freisetzung von Katecholaminen konnte bisher nicht nachgewiesen werden [51]. Kelly und Cooper [52] berichteten sogar von einer Abnahme des Noradrenalinspiegels bei depressiven Patienten, wobei die Abnahme des Spiegels mit der klinischen Verbesserung assoziiert war.…”
Section: Die Tako-tsubo-kardiomyopathieunclassified